Identification and exploration of key genes associated with radioresistance in lung adenocarcinoma - Ying Wang; Yangyang Shang; Mingyu Hua; Yidi Wang; Beina Hui; Weibin Hu; Mengke Zhu; Xiaozhi Zhang; Jing Li (Cancer Cell International)
Abstract Background Radiation resistance in lung adenocarcinoma (LUAD) remains a primary obstacle limiting radiotherapy efficacy. However, the detailed factors and molecular mechanisms influencing LUAD radiosensitivity are not fully understood. Methods Radioresistance-related genes (RRRGs) were screened by RNA sequencing and bioinformatics analysis, and a prediction model for radiotherapy efficacy was developed via LASSO-Cox regression analysis. We specifically focused on Stanniocalcin 2 (STC2) due to its prognostic significance and validated its expression through immunohistochemical staining (IHC) in pathological samples from LUAD patients. A STC2 knockdown (siSTC2) A549 cell line was created, and Western blotting, CCK8, and colony formation assays were performed to investigate STC2’s involvement in radioresistance. Results An efficacy prediction model was constructed using 6 RRRGs (FCGBP, SLCO4A1, ALDH3A1, STC2, TERT, CYP24A1). IHC analysis of 74 LUAD patients showed significantly higher STC2 expression in radiotherapy non-responders (N-Res) versus responders (Res) (p < 0.05). Patients with elevated STC2 levels experienced shorter overall survival (OS). Western blotting revealed higher STC2 expression in irradiated (IR) A549 cells compared to non-irradiated (N-IR) (p < 0.05). CCK8 assays results suggested that knockdown of STC2 resulted in a significant reduction in cell proliferation ability (p < 0.05), and colony formation assays confirmed a significant decrease in clonogenic ability of siSTC2 cells compared to controls (p < 0.05). Conclusion STC2 plays a significant role in mediating LUAD cell radioresistance, with high expression correlating with poor prognosis. Therefore, STC2 represents a promising therapeutic target for overcoming LUAD radioresistance. Clinical trial number Not applicable.